Early Warning Signs of a Mental Health Tsunami: A Coordinated Response to Gather Initial Data Insights From Multiple Digital Services Providers - Inkster, Becky; , Digital Mental Health Data Insights Group (DMHDIG) (Frontiers in Digital Health, 2021)
Introduction: The immediate impact of COVID-19 on morbidity and mortality has raised the need for accurate and real time data monitoring and communication. The aim of this study is to document initial observations from multiple digital services providers during the COVID-19 crisis, especially those related to mental health and wellbeing. Materials and Methods: We used email and social media to announce an urgent call for support. Digital mental health services providers (N=46), financial services providers (N=4) and other relevant digital data source providers (N=3) responded with quantitative and/or qualitative data insights. People with lived experience of distress, as service users/consumers, and carers are included as co-authors. Results: This study provides proof-of-concept of the viability for researchers and private companies to work collaboratively towards a common good. Digital services providers reported a diverse range of mental health concerns. A recurring observation is that demand for digital mental health support has risen, and that the nature of this demand has also changed since COVID-19, with an apparent increased presentation of anxiety and loneliness. Conclusion: Following this study, we will continue to work with providers in more in-depth ways to capture follow-up insights at regular time points. We will also onboard new providers to address data representativeness. Looking ahead, we anticipate the need for a rigorous process to interpret insights from an even wider variety of sources in order to monitor and respond to mental health needs.